"A Blending of Energies": The Concept of Energy in Contemporary Spirit Mediumship - Harvey, Sarah (Nova religio, 2025)
"Energy" is a central concept among spirit mediums in the United Kingdom. This article investigates how energy is understood by spirit mediums and the practices by which energy comes to be experienced and accepted as real. Interviews with forty such mediums revealed a shared understanding of energy that participants used reasonably consistently. We argue that the concept of energy is learned both conceptually, through metaphors, and practically, through specific trainings and practices. Drawing on cognitive anthropology, we argue that energy metaphors provide the basis for a cultural model of mediumship that both explains and forms the medium's experiences within contexts of practice. Further, this cultural model is central to their worldview, their understandings of how mediumship works, and their experiences of communicating with spirits.